Effects of Inflammatory Biomarkers (Fetuin-A and High Sensitivity C-reactive Protein) on Glycemic Control in Type 2 Diabetic Women - Al-bayati, Ali; AL-Khateeb, Shatha M.J.; Aljedda, Walaa Ahmed (Biomedical Sciences and Clinical Medicine, 2025)
Objective Inflammation plays an essential role in the development of insulin resistance and type 2 diabetes. The objective of this study was to evaluate the effects of inflammatory markers (hs-CRP and fetuin-A) on glycemic control in Iraqi women patients with type 2 diabetes, and to examine the correlation of these markers with indices of glycemic control. Methods This case-control study included 45 Iraqi type 2 diabetic female patients and 44 non-diabetic Iraqi female patients matched for age and sex as control subjects. For both patients and controls hs-CRP and fetuin-A were measured using ELISA, HbA1c by the turbidimetric immunoassay, FBG and lipid profile measures using the spectrophotometer method. Results High levels of both fetuin-A and hs-CRP were observed in diabetic patients compared to the healthy controls. hs-CRP was significantly higher in the diabetic group 3.1 ± 0.59 mg/dL than the control 1.22 ± 0.66 mg/dL and was statistically significantly correlated with the marker of glycemic control (p < 0.001). The serum level of fetuin-A in the diabetic group (768.7 ± 173.03 µg/mL) was also significantly higher than that of control (311.95 ± 94.13 µg/mL) (p < 0.001). A strong positive correlation was observed between fetuin-A concentrations with serum hs-CRP concentrations in the diabetic individuals but not in the controls. Conclusions Diabetic Iraqi women have higher inflammatory markers (fetuin-A and hs-CRP) than non-diabetic women. A strong association was observed for these inflammatory biomarkers and glycemic control in diabetic subjects.